Oncoplastic Surgery with Volume Replacement versus Mastectomy with Implant-Based Breast Reconstruction: Early Postoperative Complications in Patients with Breast Cancer - Ku, Gabriel De La Cruz; Desai, Anshumi; Singhal, Meera; Mallouh, Michael; King, Caroline; Rojas, Alexis N.; Persing, Sarah; Homsy, Christopher; Chatterjee, Abhishek; Nardello, Salvatore (Journal of Reconstructive Microsurgery, 2024)
Two common surgical approaches for breast cancer are breast-conserving surgery and mastectomy with implant-based breast reconstruction (MIBR). However, for large tumors, an alternative to MIBR is oncoplastic surgery with volume replacement (OPSVR). We performed a comprehensive analysis comparing OPSVR with MIBR, with our aim to focus on the 30-day postoperative complications between these two techniques.We conducted a retrospective cohort study using the National Surgical Quality Improvement Program (NSQIP) database from 2005 to 2020. Only breast cancer patients were included and were divided according to the surgical technique: OPSVR and MIBR. Logistic regression analysis was used to assess independent risk factors for total, surgical, and wound complications.A cohort of 8,403 breast cancer patients was analyzed. A total of 683 underwent OPSVR and 7,720 underwent MIBR. From 2005 to 2020, the adoption of OPSVR gradually increased over the years (p < 0.001), whereas MIBR decreased. OPSVR patients were older (57.04 vs. 51.89 years, p < 0.001), exhibited a higher body mass index (31.73 vs. 26.93, p < 0.001), had a greater prevalence of diabetes mellitus (11.0 vs. 5.0%, p < 0.001). They also had a higher ASA classification (2.33 vs. 2.15, p < 0.001), shorter operative time (173.39 vs. 216.20 minutes, p < 0.001), and a higher proportion of outpatient procedures (83.7 vs. 39.5%, p < 0.001). Outcome analysis demonstrated fewer total complications in the OPSVR patients (4.2 vs. 10.9%, p < 0.001), including lower rates of surgical complications (2.2 vs. 8.0%, p < 0.001) and wound complications (1.9 vs. 4.8%, p = 0.005) compared with MIBR patients. Multivariate analysis identified OPSVR as an independent protective factor for total, surgical, and wound complications.OPSVR has become a favorable technique for patients with breast cancer. Even in patients with higher comorbidities, OPSVR demonstrates safe and better outcomes when compared with MIBR. It should be considered a reasonable and safe breast surgical option in the appropriate patient.
Keywords: oncoplastic surgery; mastectomy implant-based reconstruction; outcomes; complications